2025 in review - Budget cuts, research partnerships and resilience - Taiwo, Ibukunoluwa; Pacillo, Grazia (2025)
CGIAR Climate Security 2025 in Review brings together senior leaders to reflect on a year of progress amid tightening resources and rising global risks. Hosted by Bia Carneiro, the conversation explores why climate security matters now more than ever, highlights key research and partnership wins from 2025, and examines how evidence, innovation, and collaboration can better link food, land, and water systems to peacebuilding and humanitarian action.